2021
DOI: 10.1007/s44154-021-00002-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing crop yield by using Rubisco activase to improve photosynthesis under elevated temperatures

Abstract: With the rapid growth of world population, it is essential to increase agricultural productivity to feed the growing population. Over the past decades, many methods have been used to increase crop yields. Despite the success in boosting the crop yield through these methods, global food production still needs to be increased to be on par with the increasing population and its dynamic consumption patterns. Additionally, given the prevailing environmental conditions pertaining to the global temperature increase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 167 publications
0
6
0
2
Order By: Relevance
“…Thus, enhancing our understanding of the molecular mechanism of Rubisco reactivation by Rca is critical in helping us improve the crop production, either by engineering a highly efficient enzyme or modulating the enzyme function. More details for using Rca as a target to improve crop production can be seen in this review (Wijewardene et al, 2021). It is imperative to acquire this piece of knowledge, which can be applied in crop improvements and carbon fixation efficiency in response to climate changes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, enhancing our understanding of the molecular mechanism of Rubisco reactivation by Rca is critical in helping us improve the crop production, either by engineering a highly efficient enzyme or modulating the enzyme function. More details for using Rca as a target to improve crop production can be seen in this review (Wijewardene et al, 2021). It is imperative to acquire this piece of knowledge, which can be applied in crop improvements and carbon fixation efficiency in response to climate changes.…”
Section: Discussionmentioning
confidence: 99%
“…Photosynthesis, being the primary limiting factor of yield and biomass production in plants, is controlled by complex mechanisms [118], among which the key enzyme of the CO 2 assimilation pathway, ribulose-1,5-bisphosphate carboxylase/oxygenase, or Rubisco, is regulated by Rubisco activase (RCA). Rubisco, upon binding to RCA, undergoes conformational changes in structure, thus removing the sugar phosphate derivative inhibitors that are tightly bound to both active (carbamylated) and inactive (decarbamylated) sites of Rubisco [119,120]. Even though Rubisco is a thermostable enzyme that could remain active up to 50 • C, the heat labile nature of RCA leads to the inactivation of Rubisco, thereby RCA becomes the limiting factor in the assimilation of CO 2 .…”
Section: Maintaining High Photosynthesis and High Antioxidation Capac...mentioning
confidence: 99%
“…Subsequently, Cai (2022) [137] showed that AVP1/PP2A-C5-co-overexpressing cotton outperformed wild-type cotton under drought and salt stresses in laboratory conditions and produced a higher fiber yield in field conditions. Wijewardane et al (2020, 2021) [120,138] proved that a heat-tolerant RCA from a desert shrub could be used to improve heat tolerance in transgenic plants, which prompted us to create drought-, heat-, and salt-tolerant cotton by co-overexpressing AVP1 and RCA. Subsequently, we demonstrated that AVP1/RCA-co-overexpressing cotton plants produced the highest fiber yield than wildtype and AVP1-overexpressing cotton plants under single as well as multiple stress conditions in the laboratory.…”
Section: Co-overexpression Of Two or More Genes To Improve Crop Toler...mentioning
confidence: 99%
“…Recent reviews indicate Rca as a promising target for improving crop heat tolerance in the context of climate change (Wijewardene et al ., 2021; Qu et al ., 2023; Sparrow‐Muñoz et al ., 2023). The diversity in the optimum temperature and thermal sensitivity of Rca activity has been linked with the temperature range observed in the respective plant habitat (Salvucci & Crafts‐Brandner, 2004; Yamori et al ., 2006; Carmo‐Silva & Salvucci, 2011; Shivhare & Mueller‐Cajar, 2017).…”
Section: Regulation Of Rubisco By Rubisco Activasementioning
confidence: 99%